Comprehensive Plasma Metabolome for Identification of Novel Biomarkers of Acute Myocardial Infarction - Jun Liu; Yi Yu; Qiqi Lu; Shan‐Qiang Zhang; Ji‐Cheng Li (MedComm)
ABSTRACT Metabolic disorders play a crucial role in the occurrence of acute myocardial infarction (AMI). The objective of this research was to elucidate the characteristic metabolic profile of AMI and provide potential biomarkers for AMI. This study employed a targeted metabolomics approach utilizing the Ultra Performance Liquid Chromatography Tandem Mass Spectrometry (UPLC‐MS/MS) system to identify both hydrophilic and hydrophobic metabolites present in plasma samples. Among 1498 detected metabolites, 78 were the most significantly expressed in the AMI group. Functional synergy analysis showed prominent enrichment in the pathways of steroid hormone biosynthesis, biosynthesis of unsaturated fatty acids, bile secretion, and ABC transporters. The metabolites 2‐Hydroxy‐6‐Aminopurine, 17α‐Hydroxyprogesterone, and S‐(methyl) glutathione have been identified as potential metabolic biomarkers linked to the pathogenesis of AMI. The diagnostic model that integrates these three metabolites exhibited exceptional performance in both the discovery and validation cohorts, attaining an area under the curve (AUC) value greater than 0.9. In addition, based on the follow‐up data, we also found that the three metabolites were potential predictive biomarkers for poor prognosis of AMI. This study delineated the characteristic metabolic profile of AMI and assessed the value of metabolic molecules in the diagnosis and prognosis of AMI. This may provide insights for understanding the AMI occurrence and progression.